Perspektif Notaris Kota Banjarmasin dalam Mengimplementasikan Cyber Notary - Amelia Fatmawati; Rizqa Ananda; Muhammad Haris (Fakultas Syariah UIN Antasari, 2022)
Rapidly developing technological developments affectalmost all human affairs, including business matters. Thedevelopment of this technology has led to the concept of certifyingcertificates through electronics, namely cyber notaries. Basically anotary plays a role in guaranteeing legal certainty in the civilrelations of the parties in the engagement relationship. With theterm cyber notary, notaries are faced with the ability to utilizetechnology in carrying out their notary duties. Cyber notary has abasic function as certification and authentication in electronictransactions. However, there are several dilemmas in this cybernotary, namely regarding legal certainty and knowledge of thenotary himself. In the city of Banjarmasin, business development isalso very fast, so it is important to have research on theimplementation of cyber notaries in the city of Banjarmasin. Thisstudy uses empirical legal research or also called non-doctrinal.Subjects in this study, namely notaries who are in the city ofBanjarmasin with the classification of having carried out theirduties for a minimum of five years of office. The purpose of thisresearch is to find out the perspective of a Banjarmasin city notaryregarding the urgency, readiness, and constraints in implementingcyber notary. It can be concluded that the notary perspective of thecity of Banjarmasin on the urgency of implementing cyber notarydepends on the understanding of the notary himself, not allnotaries of the city of Banjarmasin have known the concept of cybernotary. Notaries in Banjarmasin City are also not ready and areworried about several obstacles in implementing cyber notaries,such as legal certainty